When the exchange rate makes a difference: Noise Monitoring of Traffic Police in the Kathmandu Valley, Nepal - Carter, William S.; Rauniyar, Rupesh (International Journal of Occupational Safety and Health, 2011)
This study demonstrates that when measuring wide swings in noise over short time periods, Time Weighted Average (TWA) calculated results may vary significantly depending upon the exchange rate used. The 3 dBA exchange rate, the ACGIH recommended criteria, results in statistically significant higher values than the 5dBA exchange rate recommended by OSHA, when noise levels vary from 70 dBA to 120 dBA while measurements are taken. A field study of noise levels among the traffic police in the Kathmandu Valley was conducted in the spring of 2009. Sampling was done at 5 high density traffic areas on and inside the Ring Road (valley perimeter road). To collect sufficient data, hourly integrated personal and area samples were simultaneously taken with a dosimeter to identify hazardous noise areas and work locations that should be included in a hearing conservation program. This study demonstrates the importance of taking several integrated samples over short periods of time when average noise levels vary. This study likewise illustrates that area samples may not accurately reflect personal exposure, particularly when there are large variations in temporal and areal measurements. This study is the first to collect personal noise data associated with traffic noise in Nepal. Key Words: personal noise monitoring; Integrated Sampling; 3 dBA exchange rate; traffic noise; Nepal DOI: http://dx.doi.org/10.3126/ijosh.v1i1.4490 International Journal of Occupational Safety and Health, Vol 1 (2011) 7-13